2022
DOI: 10.1029/2021pa004357
|View full text |Cite
|
Sign up to set email alerts
|

Warmer Pliocene Upwelling Site SST Leads to Wetter Subtropical Coastal Areas: A Positive Feedback on SST

Abstract: The early to middle Pliocene (5.3-3 Ma) was the most recent epoch of prolonged global warmth relative to modern day. Proxy records point to several notable differences between Pliocene and modern-day climates. The Pliocene was characterized by strongly polar-amplified warming (Dowsett et al., 1994;Thompson & Fleming, 1996), with slightly smaller Antarctic ice sheets and minimal Northern Hemisphere ice coverage (Ravelo et al., 2004). The mean east-west sea surface temperature (SST) gradient in the tropical equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 89 publications
4
19
0
Order By: Relevance
“…This is supported by the moisture budget analysis presented in Fu et al. (2022), which found that both thermodynamic and dynamic processes contributed to rainfall changes in their simulations. Because SST anomalies in the PRISM3 data set are muted south of Baja California, δ D p is slightly depleted in that region, differing from our record from site 475 (Figure 2, Figure S5 in Supporting Information ).…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…This is supported by the moisture budget analysis presented in Fu et al. (2022), which found that both thermodynamic and dynamic processes contributed to rainfall changes in their simulations. Because SST anomalies in the PRISM3 data set are muted south of Baja California, δ D p is slightly depleted in that region, differing from our record from site 475 (Figure 2, Figure S5 in Supporting Information ).…”
Section: Resultssupporting
confidence: 66%
“…A recent modeling study hypothesized that warmer California margin temperatures in the Pliocene resulted in expanded and enhanced summer convection (Fu et al., 2022). This hypothesis implies that the evolution of the Plio‐Pleistocene NAM should track coastal temperatures on the California Margin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have proposed that weaker atmospheric circulation in response to the different ocean surface temperature patterns of the Pliocene reduced meridional and zonal temperature gradients (Molnar and Cane, 2002;Burls and Fedorov, 2017). Another recent hypothesis argues for more enhanced convergent monsoonal circulation developed over late boreal summer due to increased SST in the Pliocene (Fu et al, 2022). Lastly, strengthened southwesterly moisture delivery could have resulted in greater wintertime precipitation that fed the southwest USA lakes (Ibarra et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…2c), and thereby additionally support the classic picture of a thermally-driven intensification of the mid-Holocene NAM. Furthermore, paleoclimatic investigations of intervals featuring pronounced global changes, such as the Last Glacial Maximum (∼21,000 years before present) and the Pliocene (5.3-3 million years before present) further establish the importance of thermal gradients in modulating NAM variability -be it via atmosphericallymediated meridional temperature contrasts over the North American continent [12] or via coastal land-sea temperature gradients [13].…”
Section: Matters Arisingmentioning
confidence: 99%